2012
DOI: 10.1261/rna.033399.112
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for developing a hammerhead ribozyme for selective RNA cleavage depending on substitutional RNA editing

Abstract: Substitutional RNA editing plays a crucial role in the regulation of biological processes. Cleavage of target RNA that depends on the specific site of substitutional RNA editing is a useful tool for analyzing and regulating intracellular processes related to RNA editing. Hammerhead ribozymes have been utilized as small catalytic RNAs for cleaving target RNA at a specific site and may be used for RNA-editing-specific RNA cleavage. Here we reveal a design strategy for a hammerhead ribozyme that specifically reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Our results indicated that the saturation value and cleavage rate were similar to those obtained in the reaction against the HTR2C RNA fragment. In the case of minHHR, the in vitro trans-cleavage constant against the long substrate was >100-fold lower than that against the short substrate (Campbell et al 1997;Hormes and Sczakiel 2002;Fukuda et al 2012). The reason for this decrease in cleavage activity may be an inability to form the proper active conformation through base-paired, nonspecific interactions with ribozyme nucleotides.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our results indicated that the saturation value and cleavage rate were similar to those obtained in the reaction against the HTR2C RNA fragment. In the case of minHHR, the in vitro trans-cleavage constant against the long substrate was >100-fold lower than that against the short substrate (Campbell et al 1997;Hormes and Sczakiel 2002;Fukuda et al 2012). The reason for this decrease in cleavage activity may be an inability to form the proper active conformation through base-paired, nonspecific interactions with ribozyme nucleotides.…”
Section: Discussionmentioning
confidence: 97%
“…The results of B and C are presented as averages and standard deviations from three independent experiments. developed a strategy for HHR cleavage of target RNA when a specific site is subjected to A-to-I RNA editing (Fukuda et al 2012). In this report, we next developed an HHR with an inverse sequence specificity, i.e., one that cleaves substrate RNA only at unedited target sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have recently shown promising results in employing RNA editing to correct single point mutations, both in cells (1921, 23, 24, 2729, 31, 3335, 42, 5153) and in animal models (25, 26, 30, 32). These studies have revealed the following major weaknesses in the system: (a) editing can never reach 100% efficiency; (b) off-target (or bystander) editing is more of a problem than initially expected (though it can be ameliorated) (42, 46, 47).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro selection. In vitro selection was basically performed using the methods reported by Lockett et al 52 and Fukuda et al 53 the 3′-biotinylated substrate strand (200 pmol) was incubated with Dynabeads™ MyOne™ Streptavidin C1 beads (Thermo Fisher Scientific Inc., Waltham, MA, USA) in a wash buffer (50 mM HEPES, pH 7.5, 1 M NaCl and 0.01% Tween 20) for 1 h at 25°C. After three times wash with the wash buffer, the N16 library (200 pmol) was annealed to the substrate by heating at 95°C for 5 min and gradually cooling to 4°C.…”
Section: Methodsmentioning
confidence: 99%